(untitled) (Fiep Bulletin - online, 2014)
Hospitalization, either for reason of chronic illness or not, can bring damages to the child quality of life. To deal with this situation, the therapeutic recreation can works as strategy to lighten up the decurrent damages. Thus, this study had as objective to evaluate the quality of life of children with hospitalized chronic diseases, participant of therapeutic recreation. The study was of the transversal descriptive type. The sample was composed by 50 children of both genders (6 to 12 years old), interned in the Hospital da Criança Santo Antônio de Porto Alegre, RS, Brazil. Inventory AUQUEI (MANIFICAT and DAZORD was applied apud ASSUMPÇÃO JR. et. Al, 2000), that evaluates the quality of life in infancy. The results had indicated no significant difference among the averages of the AUQUEI between the sexual sorts (U = 292; p = 0,717). It was possible to conclude that the children of the sample possess a good quality of life, although passing for difficult moments during the internment, what can be the result of the positively association between practical of ludic and recreative activities and the familiar support.